RETRACTED: Ph-triazole as a therapeutic agent for pancreatic cancer: Synthesis, in silico, and in vitro evaluation - Ningbo Zhang; Xingxing Li; Fangyuan Li; Jianjiang Jin; Ting Zheng; Li Zhou (PLoS ONE, 2025)
The current study investigated the therapeutic potential of Ph-triazole in silico and in vitro against pancreatic cancer. Common targets between Ph-triazole and pancreatic cancer, notably P53 protein, were identified using the venny 2.1.0 tool and imported into the String database to construct the protein-protein network. Box plot revealed that the most prominent hub gene TP53 is strongly up-regulated in pancreatic tumor tissues (N = 179) compared to normal tissue samples (N = 171), and stage plots confirmed that its upregulation is found during all four stages of the disease. Survival analysis of the pancreatic cancer patients revealed a strong correlation between TP53 gene overexpression and low overall survival and disease-free survival. Molecular docking showed that Ph-triazole exhibits a strong binding affinity for P53 protein. In vitro data also confirmed the anti-proliferative effect of Ph-triazole in pancreatic cancer cell models. Therefore, Ph-triazole can act as an anti-proliferative agent for pancreatic cancer and needs to be investigated further by in vivo studies.